Physiological and Biochemical Effect of Elevated Night Temperature Stress on Bread Wheat (Triticum aestivum L.) - Ahmad, Md. Afjal; Prakash, Pravin; J. P. Srivastava; K. Dujeshwer; Singh, Anil K.; H. S. Jatav (Emirates Journal of Food and Agriculture, 2023)
A laboratory experimentation was done in the Department of Plant Physiology, Institute of Agricultural Sciences, Banaras Hindu University to evaluate elevated night temperature effect in wheat (Triticum aestivum L.) to see the response in some antioxidant and biochemical parameters in two wheat cultivars viz. HUW-234 (comparatively tolerant to heat stress) and sonalika (comparatively susceptible to heat stress). A significance difference was recorded in the parameters pertaining to antioxidant system includes catalase, SOD and APX activity were found to increase substantially when the plants kept under stress conditions (250C/ 240C day and night temperature) than the plants kept under controlled condition (250C/150C day and night temperature). The percent increase in the antioxidant enzyme activity was found to be more in the tolerant genotype (HUW-234) than in the susceptible genotype (Sonalika). There was 23.52 % increase was reported in the catalase activity by tolerant genotype when kept under stress conditions than those kept under control. Significant reductions were reported in most of the photosynthetic and membrane parameters viz., chlorophyll ‘a’, chlorophyll ‘b’ and membrane thermostability index. Similar percent reduction was reported with respect to biochemical parameters (total protein content, starch content and soluble sugar content) in the susceptible variety kept under high night temperature regime. Based on the pooled data of two-year experimentation it can be concluded that variety HUW-234 was found to be more tolerant than variety sonalika to HNT stress. Key Words: High night temperature, Wheat, Catalase activity, Anti-oxidant system.